The art of stop-motion animation - Priebe, Ken A. (Thomson Course Technology PTR, 2007)
Through the magic of stop-motion animation, inanimate objects seem to spring to life. With true artistic passion and finesse, a stop-motion film evokes the nostalgia of childhood when imagination could bring toys to life. Stop-motion retains the art and performance that are the heart and soul of captivating animation. Beginning with a history of stop-motion animation, The Art of Stop-Motion Animation takes you on a unique journey - uncovering the origins of this art form and examining what continues to draw viewers to these films. Through several hands-on exercises, you'll learn how to create puppets and how to bring them to life as you create your own stop-motion film. Interviews with industry professionals offer a fascinating, behind-the-scenes look into the undying art form of stop-motion animation.